2019
DOI: 10.11149/jkaoh.2019.43.3.136
|View full text |Cite
|
Sign up to set email alerts
|

Financial estimate of light-curing composite resin treatment after National Health Insurance Service coverage

Abstract: This study aimed to estimate the financial budget of light-curing composite resin fillings based on the expanded coverage of the National Health Insurance Service (NHIS), called "Moon Care." Methods: The estimated population with dental caries and the amount of light-curing composite resins used were determined. The fees for the resin fillings per tooth were considered for the calculations. The expected budget for the next five years for children and adolescents aged 5-12 and 5-19 years were calculated. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that the preference for and usage of composite resins are continuously growing. As the use of lightcuring composite resin to treat dental caries in children under the age of 12 is ensured, the demand for the composite resin is expected to rise 16) . However, studies have reported that composite resins are greatly affected by the oral environment, along with enamel.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the preference for and usage of composite resins are continuously growing. As the use of lightcuring composite resin to treat dental caries in children under the age of 12 is ensured, the demand for the composite resin is expected to rise 16) . However, studies have reported that composite resins are greatly affected by the oral environment, along with enamel.…”
Section: Introductionmentioning
confidence: 99%